1968
DOI: 10.1002/aja.1001230107
|View full text |Cite
|
Sign up to set email alerts
|

Observations on epidermal differentiation in the fetal rat

Abstract: Study of fetal rat epidermis has revealed the presence of a single layer of nonkeratinizing cells, the periderm, that covers the free surface of the skin during embryonic life. The periderm resembles structurally the epithelium lining the amniotic cavity, and the two are believed to be similar in function and embryonic origin.Observations of keratinization have shown that keratohyalin granules formed initially during fetal life may differ in structure from those formed during later fetal life and in the adult.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

1971
1971
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 21 publications
4
39
1
Order By: Relevance
“…6). These findings are in accordance with those of Bonneville [1968], Beneath these two layers a stratum corneum is present. In this layer an enormous diversity in cell height and in electron opacity is striking.…”
Section: -To 21-day-old Fetal Rat Skinsupporting
confidence: 93%
See 3 more Smart Citations
“…6). These findings are in accordance with those of Bonneville [1968], Beneath these two layers a stratum corneum is present. In this layer an enormous diversity in cell height and in electron opacity is striking.…”
Section: -To 21-day-old Fetal Rat Skinsupporting
confidence: 93%
“…This was chosen since in fetuses of this age we saw no sign of keratinization with light microscopy [Bauer and K u y pe r , in press]. This is in agreement with the findings of H anson [ 1947] but not with the observations of Bonneville [ 1968] who found that keratinization starts at about the i 1th day of fetal life. The reason for this difference is discussed later.…”
Section: Observationssupporting
confidence: 82%
See 2 more Smart Citations
“…The skin of the face at El6 consists of two layers of proliferative ectodermal cells, the cuboidal cells of the epidermis and a n outer layer of flattened cells called the periderm (Bonneville, 1967). Figure 41 shows immunoreactivity associated with the skin of a n E l 6 embryo.…”
Section: Comparison Of El6 and Adult Tissuesmentioning
confidence: 99%